Narrative of Women and Sexual Violence in Indonesian Law - Katjasungkana, Soka Handinah (Yayasan Jurnal Perempuan, 2016)
Power constellations perspective about sexuality of women and women’s body in the context of legislative advocacy Elimination of Sexual Violence Bill which is currently being carried out by a network of women’s movement representing how women and women’s body interpreted. This was reflected in the legal product and legal draft which being advocated, from the recognition of who is considered to be the victims should be protected and who is the perpetrator who should be subject to sanctions. The comparison between the Law No. 44 Year 2008 on Pornography as an initiative of the Parliament members with a legal draft on the Elimination of Sexual Abuse, can describe the power constellation of thinking about women’s sexuality. Because of a legal product shows the ideology of the manufacturer o f the law itself, in particular the law maker (government and parliament) as well as more broadly is the society.